REPRESENTATIONS OF BROTHERHOOD ND EQUAL OPPORTUNITY IN DANNY BOYLE'S SLUMDOG MILLIONAIRE MOVIE (2008) : A SEMIOTIC APPROACH - IMTIHAN , NAJJAHUL (2010)
This study describes representation of brotherhood and equal opportunity in Slumdog Millionaire movie based on semiotic approach. After analyzing this movie, the writer finds the kinds of representation of brotherhood and equal opportunity in Slumdog Millionaire movie. The study belongs to the qualitative study. In the method, there are two types of data source which are used by the writer, namely primary data source secondary data source. The primary data source and the object is the movie of Danny Boyle's Slumdog Millionaire itself, meanwhile secondary one is other data related to the study. The writer collects the data from both, primary and secondary data sources in a short of document as evidence. The study uses library research to collect the data, the collected data are analyzed by means descriptive analysis. Having analyzed this movie, the writer draws some conclusion. First, structural elements of Slumdog Millionaire movie built in good production. Second there are many representation of brotherhood and equal opportunity in Slumdog Millionaire movie. They are represented in the title, characterization, setting, plot sequence, and cinematography. Third, there are some criticism reflected in Slumdog Millionaire movie. In Slumdog Millionaire movie, the director wants to say that everyone has equal rights and equal opportunity to choose their own way for success and happiness.